Digitale Lernwelt - SERIOUS GAMES Einsatz in der beruflichen Weiterbildung - Metz, Maren; Theis, Fabienne (wbv Publikation, 2011)
In the context of continuous professional development the use of Serious Games becomes increasingly important. In the practice, the use of digital learning games has been rarer to date; however, there is an increasing trend noticeable, too. This anthology contributes to the establishment of Serious Games as an important and sustainable method within continuous professional development and to the presentation as a significant and future-proof area of development. The didactic conceptions of the digital learning games are tested with regard to the learning, the development of competences, reflections and transfer. Furthermore, different fields of use of Serious Games within professional practice are presented. Der Einsatz von Serious Games gewinnt im Kontext der beruflichen Weiterbildung zunehmend an Bedeutung. In der Praxis ist die Anwendung von digitalen Lernspielen bisher eher selten, dennoch ist eine steigende Tendenz zu erkennen. Dieser Sammelband trägt dazu bei, Serious Games als wichtige und nachhaltige Methode in der beruflichen Weiterbildung zu etablieren und als ein bedeutsames und zukunftsweisendes Entwicklungsfeld darzustellen. Die didaktischen Konzeptionen der digitalen Lernspiele werden im Hinblick auf Lernen, Kompetenzentwicklung, Reflexion und Transfer geprüft. Außerdem werden verschiedene Einsatzbereiche von Serious Games in der beruflichen Praxis vorgestellt